Anthelmintics in the future: current trends in the discovery and development of new drugs against gastrointestinal nematodes - Zajíčková, Markéta; Nguyen, Linh Thuy; Skálová, Lenka; Raisová Stuchlíková, Lucie; Matoušková, Petra (Drug discovery today, 2020)
The control of gastrointestinal nematodes (GINs), the most abundant and serious parasites of livestock, has become difficult because of the limited number of available drugs and fast development of drug resistance. Thus, considerable efforts have been devoted to developing new anthelmintics that are efficient against nematodes, especially resistant species. Here, we summarize the most recent results using various approaches: target-based or high-throughput screening (HTS) of compound libraries; the synthesis of new derivatives or new combinations of current anthelmintics; the repurposing of drugs currently approved for other indications; and lastly, the identification of active plant products. We also evaluate the advantages and disadvantages of each of these approaches.
Keywords: Gastrointestinal Diseases; biologické přípravky; Nematode Infections; Anthelmintics; Drug Repositioning; Drug Discovery; anthelmintika; zvířata; gastrointestinální nemoci; Humans; objevování léků; nematodózy; přehodnocení terapeutických indikací léčivého přípravku; Biological Products; Drug Combinations; fixní kombinace léků; lidé; Animals